2019
DOI: 10.1016/j.ijpharm.2019.118770
|View full text |Cite
|
Sign up to set email alerts
|

Wetting of binary powder mixtures

Abstract: The wetting process involved when a liquid droplet comes into contact with a mixture of particles is a complex phenomenon which is often understood by reference to Cassie-Baxter theory. However, various authors have applied the Cassie-Baxter theory for the prediction of contact angles on two-component mixtures without success. We hypothesise that the main difficulty in applying the Cassie-Baxter theory to mixtures is that if the particles differ in size, it is possible for the small particles to coat the large… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…The lowest contact angle values are obtained for samples containing magnesium particles (CA-HAp-Mg and CA-Mg), which proves that by adding them, hydrophilic surfaces favorable for biological integration are obtained ( Figure 10 ). It is well known that when a liquid droplet comes into contact with a mixture of different particles, such as in our case (HAp and Mg particles), a complex contact angle behaviour can be observed [ 67 ]. As an analytical tool, the Cassie–Baxter theory can be used.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The lowest contact angle values are obtained for samples containing magnesium particles (CA-HAp-Mg and CA-Mg), which proves that by adding them, hydrophilic surfaces favorable for biological integration are obtained ( Figure 10 ). It is well known that when a liquid droplet comes into contact with a mixture of different particles, such as in our case (HAp and Mg particles), a complex contact angle behaviour can be observed [ 67 ]. As an analytical tool, the Cassie–Baxter theory can be used.…”
Section: Resultsmentioning
confidence: 99%
“…As an analytical tool, the Cassie–Baxter theory can be used. Mundozah et al [ 67 ] adapted this model by considering the average particle diameter. They showed that in the case of a mixture formed from larger particles (i.e., Mg powder) and small particles (i.e., HAp powder), if the larger particle diameter is higher than a critical volume fraction, the surface wettability could change considerably due to the fact that partial coverage of larger particles by the small ones appears.…”
Section: Resultsmentioning
confidence: 99%
“…One of the common equipment items evaluated to perform continuous granulation are the twin screw granulators (TSGs) (Mundozah et al, 2018;Silva et al, 2018). The advantage of this equipment is the flexibility offered from the high number of possible working environments achieved by changing different sections of the screw assembly, different segment geometries or feed port locations (Dhenge et al, 2011;Djuric and Kleinebudde, 2008).…”
Section: Introductionmentioning
confidence: 99%